United States, China and The Dispute For Global Hegemony: a Comparative Analysis - Vázquez Rojo, Juan (HUMAN REVIEW. International Humanities Review / Revista Internacional de Humanidades, 2022)
The trade and technological war initiated in 2018 between China and the United States has increased interest in the possible hegemonic succession. In this paper, starting from the concept of interstate hegemony, a comparative analysis of the material capabilities of each power in five areas: productive, technological, commercial, monetary-financial and military. This analysis makes it possible to quantify whether China can surpass the United States. As a result, it is concluded that China is far from surpassing the United States in the military and monetary-financial areas, but it can compete in the productive, commercial, and certain critical technological sectors.